: Experiences With Pharmacy-Based PrEP Delivery Among Adolescent Girls and Young Women in Kisumu, Kenya - Melissa Vera PhD; Elizabeth Bukusi MPH, PhD; Pauline Achieng; Helen Aketch; Evelyne Araka; Jared M. Baeten MD, PhD; Kristin Beima-Sofie MPH, PhD; Grace John-Stewart MD, PhD; Pamela K. Kohler MPH, PhD; Melissa L. Mugambi MD, PhD; Bernard Nyerere; Josephine Odoyo; et al. (Journal of the International Association of Providers of AIDS Care, 2023)
Introduction Many Kenyan adolescent girls and young women (AGYW) with behaviors associated with HIV acquisition access contraception at retail pharmacies. Offering oral pre-exposure prophylaxis (PrEP) in pharmacies could help reach AGYW with PrEP services. Methods We piloted PrEP delivery at 3 retail pharmacies in Kisumu, Kenya. AGYW purchasing contraception were offered PrEP by nurses with remote prescriber oversight. AGYW who accepted were provided with a free 1-month supply. We conducted in-depth interviews with AGYW 30 days postobtaining PrEP. Transcripts were analyzed to explore experiences of AGYW accessing PrEP at pharmacies. Results We conducted 41 interviews. AGYW preferred pharmacies for accessing PrEP and they were willing to pay for PrEP even if available for free at clinics. Reasons for this preference included accessibility, lack of queues, and medication stockouts, privacy, anonymity, autonomy, and high-quality counseling from our study nurses. Conclusions Pharmacies may be an important PrEP access option for this population.